Inhibition of tumor growth and metastasis with antisense oligonucleotides (Cantide) targeting hTERT in an in situ human hepatocellular carcinoma model - Lin Ru-xian; Tuo Chao-wei; Lü Qiu-jun; Zhang Wei; Wang Sheng-qi (Acta Pharmacologica Sinica; Vol 26, No 6 (June 2005): Acta Pharmacologica Sinica, 2016)
Aim: To evaluate the in vivo antitumor effects of Cantide and the combined effect with 5-fluorouracil. Methods: An in situ human hepatocellular carcinoma model was established in mice livers orthotopically. Drugs were administered intravenously and tumor sizes were monitored with calipers. Plasma alpha-fetoprotein (AFP) were detected by radiation immunoassay. Morphology of tumors was evaluated by hematoxylin-eosin (H&E) staining of histological sections. Human telomerase reverse transcriptase (hTERT) protein levels were detected by Western blotting. Results: Cantide significantly inhibit in situ human hepatocellular carcinoma growth in mice with a 75 and 50 mgdotkg-1dotd-1 administration of Cantide compared to the saline group in a dose-dependent manner, which included injecting Cantide 25 mgdotkg-1dotd-1-VS mgdotkg-1dotd-1 by iv for 20 d after surgically removing the tumor in liver. Cantide was also found to prevent tumor recurrence in the liver and metastasis in the lung, showing a dose-dependent response. When Cantide was administered by iv combined with 5-fluorouracil, it resulted in a significant reduction in tumor growth compared to either agent alone treatment group. After the treatment with Cantide alone or combined with 5-fluorouracil, plasma AFP concentration decreased in a dose-dependent manner. Conclusion: These results demonstrated that Cantide was an effective antitumor antisense oligonucleotide in vivo and has the potential to be developed into a clinical anti-cancer drug.